2017
DOI: 10.1002/adma.201703800
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Efficient Lead‐Free Formamidinium Tin Triiodide Perovskite Solar Cells via a Sequential Deposition Route

Abstract: Recently, the evolved intermediate phase based on iodoplumbate anions that mediates perovskite crystallization has been embodied as the Lewis acid-base adduct formed by metal halides (serve as Lewis acid) and polar aprotic solvents (serve as Lewis base). Based on this principle, it is proposed to constitute efficient Lewis acid-base adduct in the SnI deposition step to modulate its volume expansion and fast reaction with methylammonium iodide (MAI)/formamidinium iodide (FAI) (FAI is studied hereafter). Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
229
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(239 citation statements)
references
References 66 publications
8
229
0
2
Order By: Relevance
“…The perovskite films based on DMSO and MAAc showed inconspicuous absorption band edges as a result of deep charge traps and high defect density (Figure 2b), which caused by poor film morphology leading to the oxidation of Sn 2+ . [31] In contrast, the "L-I" based films behaved the apparent absorption band edge at about 980 nm, indicating its higher quality film and better crystallinity, which is in agreement with the discussion above. Moreover, "L-I" based films exhibit the higher PL intensity, which further demonstrated the low defect density.…”
Section: Doi: 101002/advs201800793supporting
confidence: 87%
See 1 more Smart Citation
“…The perovskite films based on DMSO and MAAc showed inconspicuous absorption band edges as a result of deep charge traps and high defect density (Figure 2b), which caused by poor film morphology leading to the oxidation of Sn 2+ . [31] In contrast, the "L-I" based films behaved the apparent absorption band edge at about 980 nm, indicating its higher quality film and better crystallinity, which is in agreement with the discussion above. Moreover, "L-I" based films exhibit the higher PL intensity, which further demonstrated the low defect density.…”
Section: Doi: 101002/advs201800793supporting
confidence: 87%
“…The LDRP perovskites exhibited low selfdoping effect, suppressed ion migration, and excellent oriented growth over 3D perovskite due to this multiple-quantum-well structure, [27][28][29][30] which is benefit to inhibit the defect density in Sn perovskites. [24,27,31] Furthermore, the investigation on controlling growth of high-quality crystals with large domain by management of crystallization kinetics of Sn perovskite films has not been yet demonstrated. Furthermore, Ning et al [27] utilized the PEA to form the LDRP Sn perovskite with highly oriented crystal growth.…”
Section: Doi: 101002/advs201800793mentioning
confidence: 99%
“…The critical role of the SnF 2 addition has been confirmed by later studies and reviewed recently by Gupta et al [66] More recently, formamidinium tin iodide (FASnI 3 ) was introduced to replace MASnI 3 due to improved film morphology and electrical properties and has been gradually become the most popular choice for Sn perovskite solar cells. [69] Zhao et al employed mixed organic-cation tin iodide (FA 0.75 MA 0.25 SnI 3 ) absorber for the inverted planar cells and reported a PCE of 8.12%. [67] Liao et al reported inverted planar FASnI 3 solar cells using a solvent-engineering method to achieve a high PCE of 6.22%.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[2][3][4][5] Theoretical calculations indicate that the perovskite crystal structure is preserved after metal cation substitution. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Rapid oxidation of Sn 2+ to Sn 4+ in ambient atmosphere dopes the perovskite layer into high conductivity,r esulting in severe electrical shunting. [2][3][4][5][6][7] Unfortunately,p ower conversion efficiencies (PCEs) obtained from Sn-based PSCs are much lower than that of their Pb counterpart.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Rapid oxidation of Sn 2+ to Sn 4+ in ambient atmosphere dopes the perovskite layer into high conductivity,r esulting in severe electrical shunting. Combined, as imple and reliable protocol for fabricating efficient Snbased PSCs is established, with the best device reaching aPCE of 7.2 %.Although FASnI 3 is commonly used as the Sn perovskite absorber layer, [18][19][20][21][22][23] we have demonstrated that alignment between the valence band (VB) of FASnI 3 perovskite and the highest occupied molecular orbital (HOMO) level of commonly used hole-transporting materials (HTM:PEDOT:PSS, Spiro-OMeTAD,e tc.) [18] Despite the clear need to improve device performance,only alimited number of groups are investigating Snbased PSC at present.…”
mentioning
confidence: 99%